Studi pendahuluan pada standar kemampuan tenaga kerja rantai pasok konstruksi - Moh Nur Sholeh; Shifa Fauziyah; Undayani Cita Sari (Jurnal Proyek Teknik Sipil, 2021)
The ability of workers in construction supply chain section has not been strongly standardized as to their role and performance, especially in Indonesian project. The purpose of the research is to conduct a preliminary study of workforce capability standards in construction supply chain management. The initial standard was adopted from Supply Chain Operations References (SCOR) 12.0. The results showed that the ability element was the highest priority with 50%. Whereas the most standard worker needs to be mastered is to schedule product shipments with 18% and the lowest value is to do exception management in construction with 1%. Research recommendations are that workers need to attend every training on construction supply chain workers' standards in order to have complete capabilities.